Nuclear Imaging to Detect Diaphragmatic Perforation as a Rare Complication of Microwave Ablation - Stephanie Cull; Gebran Khneizer; Abhishek Krishna; Razi Muzaffar; Sameer Gadani; Zafar Jamkhana (Case Reports in Critical Care)
Acquired diaphragmatic perforation leading to massive hepatic hydrothorax and respiratory failure is a rare complication of microwave ablation (MWA) of hepatocellular carcinoma (HCC). Imaging modalities to detect pleuroperitoneal communication remain poorly described. We report a nuclear imaging technique used to efficiently diagnose and locate diaphragmatic defects. A 57-year-old male with cirrhosis and HCC presented with respiratory distress after undergoing MWA of a HCC lesion. He was admitted to the intensive care unit for noninvasive positive pressure ventilator support. Chest radiography revealed a new large right pleural effusion. Large-volume thoracentesis was consistent with hepatic hydrothorax. The fluid reaccumulated within 24 hours; therefore an acquired diaphragmatic perforation induced by the ablation procedure was suspected. To investigate,  99mTechnetium-labeled albumin was injected into the peritoneal cavity. The tracer accumulated in the right hemi thorax almost immediately. The patient then underwent transjugular intrahepatic portosystemic shunting in efforts to relieve portal hypertension and decrease ascites volume. Unfortunately, the patient deteriorated and expired after few days. Although diaphragmatic defects develop in cirrhotic patients, such small fenestrations do not normally lead to rapid development of life-threatening pleural effusion. MWA procedures can cause large diaphragmatic defects. Immediate detection of this complication is essential for initiating early intervention.